Doing less is better : challenges in complex polytrauma management - case report - Farah NA,; Johar MJ,; Ismail Mohd Saiboon, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Damage control resuscitation, characterized by hemostatic resuscitation with blood products, rapid arrest of bleeding and when possible, permissive hypotension with restricted fluid load form a structured approach in managing a polytrauma patient. When complicated with traumatic rhabdomyolysis however, permissive hypotension strategy may cause more harm resulting in subsequent ischaemicreperfusion injury and acute kidney injury. We present a case involving a 20-yearold man who was rolled over by a lorry and sustained an open unstable pelvic fracture with vascular injury and left lower limb ischaemia. Permissive hypotension strategy was pursued for 4 hours prior to bleeding control in OT. This was followed by protracted surgery of 6 hours. Coagulopathy, acute kidney injury and rhabdomyolysis ensued in the post-operative period and patient succumbed to his injury on Day 3 post-trauma. Challenges and pitfalls in managing a complex polytrauma patient and recent evidences on damage control resuscitation is discussed.